SOME TRADITIONAL NAMES IN TOPONIMICS - Seitniyazov K. M. (Galaxy International Interdisciplinary Research Journal, 2023)
To create a scientific understanding of the history of geographical names that have become traditional in the Uzbek language, the peculiarities of writing, international requirements for them, established traditions regarding translatable and untranslatable names.